Tropical cyclones and their impact on stock market returns and volatility - De Guzman, Christian Louis G.; Fabula, Jewel Kyle M.
The Philippines is one of the world’s most disaster-prone countries. These disasters have an impact on the economy, which may influence the stock market returns and volatility. We used an ARMAX-EGARCH model to analyze the impact of tropical cyclones on the Philippine Stock Exchange Index (PSEi) and some sectoral indices (Financial, Industrial, Property, Mining and Oil). As an extended analysis, we also control for the disaster location in 1-day, 5-day, 10-day, and 15-day event windows. The results show that tropical cyclones that affected Visayas have significant same-day negative impacts on the average market returns. In contrast, tropical cyclones that affected Mindanao have significant same-day positive impacts on the average market returns. Meanwhile, the effect of tropical cyclones on sectoral market returns and volatility can be positive, negative, or no effect, depending on affected regions of the disaster, market sector considered, or event window being analyzed. Overall, our results indicate that location and time are salient factors in assessing the impact of tropical cyclones on the stock market as well as the sector in which the analysis is performed.